Fungal Genomics - Dunlap, Jay C. (Advances in genetics, 2007)
The sequencing of several fungi genomes has spurred major advances in the field. Fungal genomics has been having a pivotal impact on applied research in agriculture, food sciences, natural resource management, pharmaceuticals, and biotechnology, as well as to basic studies in the life sciences. This volume covers exciting new developments in this growth field, from genomic analysis to human fungal pathogen genomics, comparative genomics of fungi, and the genomics of fungal development. * Includes information on aspergillus genomes* Discusses sex and its ro.